Sex distinctive patterns in the association between serum bicarbonate and uric acid levels among healthy adults. Qatar biobank data - Ibrahim, Wisam Nabeel; Shi, Zumin; Abdallah, Atiyeh M.; Abu-Madi, Marawan Abdelhamid (Frontiers in Medicine, 2023)
Background Uric acid is the final product of purine metabolism and is a potent plasma antioxidant but with pro-inflammatory effects. At high levels, it may increase the risk of developing multiple chronic diseases, such as gout, atherosclerosis, hypertension, and renal diseases. The aim of this study was to assess the sex-specific association between serum bicarbonate and uric acid levels among healthy adults. Methodology This retrospective cross-sectional study included 2,989 healthy Qatari adults (36.4 ± 11.1 years) from the Qatar Biobank database. Serum uric acid and bicarbonate levels were estimated alongside other serological markers. Participants free from chronic diseases were divided into four quartiles based on serum bicarbonate levels. The sex-specific relationship between serum bicarbonate and uric acid levels was assessed through univariate and multivariate analyses. Results In men, low serum uric acid levels were significantly associated with higher quartiles of serum bicarbonate levels after adjusting for age. The association remained significant after further adjustment for BMI, smoking, and renal function. The subgroup analysis using the restricted cubic spline method confirmed a significant dose–response association between the variation coefficients of uric acid by serum bicarbonate level in men with adjustments for age, BMI, smoking, and renal function. In women, no significant association was found between quartiles of serum bicarbonate and uric acid levels following the same adjustments. However, using the restricted cubic spline method, a significant bidirectional relation was demonstrated between serum bicarbonate and the variation coefficients of uric acid that were positive for serum bicarbonate levels below 25 mEq/L and negative at higher levels. Conclusion Serum bicarbonate levels are linearly associated with reduced serum uric acid levels among healthy adult men, which may be a potential protective factor against hyperuricemia-related complications. Further research is needed to determine the underlying mechanisms.